18F-FDG PET/CT is an ideal imaging modality for the early diagnosis of relapsing polychondritis: A case report. Issue 30 (July 2017) - Wang, JianJie; Liu, XiaoFei; Pu, Chaoyu; Chen, Yan
Abstract: Background: Relapsing polychondritis (RP) is a rare autoimmune disease of unknown etiology that may affect multiple cartilage throughout the body. Case report: We report on a middle-aged man presented with cough, chest tightness, and fever of unknown origin, 18F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) was performed. And the imaging shows multiple increased FDG accumulation in tracheobronchial tree and all intercostal cartilages, as well as in nasal, right auricule, laryngeal cartilage. Based on the findings, the diagnosis of RP was made. Conclusion: Our case demonstrates that FDG PET/CT is an useful diagnostic tool to accurately determine the extent of inflammation throughout the body and to guiding the selection of a biopsy site.